Effects of repeated water and domestic bleach immersion on kenaf fibre-reinforced polyropylene composites - Wan Hussin, Wan Mohamad Haniffah (2011)
Most applications of natural fibre composite intended for environment free from water in order to avoid degradation in mechanical properties due to high water absorption property of the natural fibre composites. The aim of this research is to study the pattern of liquid content of kenaf fibre reinforced polypropylene composites and general changes in tensile properties caused by cyclic immersion and also the difference between cyclic and continuous immersion effect on tensile properties of the composites. The pattern of liquid contents in the composites were compared between 40 and 60% fibre loadings composites under cyclic immersion for 4 cycles, where each cycle consist of 3 days of immersion and 4 days of conditioning in room temperature (28°C and 55% humidity). The liquids used for immersion were water and bleach (16.17% v/v). Results shown that, for both fibre loadings, liquid content pattern for composites immersed in bleach deviate from composites under water immersion. The deviations were more obvious when numbers of cycles were increased Although liquid contents in composites were increased from cycle to cycle; for the same total duration of immersion, the amount of liquid content in composites immersed under cyclic immersion were less than continuous immersion for all composites. Among 3 factors studied in cyclic immersion; statistical analysis has shown that fibre compositions in the composites and cycle of immersion gave significant influence on tensile strength of the composites while liquid of immersion (difference between water and bleach) only significant on fourth cycle of immersion. On the other hand, tensile moduli were influenced by all the studied factors. As a conclusion, bleach did influence tensile modulus of the composites but did not significantly influenced tensile strength of the composites until the forth cycle of immersion. The type of immersion (cyclic and continuous immersion) also influenced tensile properties of the composites. Statistically, tensile strength of the composites showed significant difference between cyclic and continuous immersion only occurred for composite immersed in bleach. Nevertheless statistical analysis showed that tensile moduli of the composites were not significant between cyclic and continuous immersion. The results conclusively showed that types of immersions (continuous and cyclic immersion) only cause significant difference in tensile strength of composites immersed in bleach.